Virtual Geographic Information System (VGIS) from ITM main entrance to Kolej Seroja / Burhannuddin Abd. Hamid - Abd. Hamid, Burhannuddin (1999)
The purpose of this project is to give a guide and information to the visitors who wanted to know about Institut Teknologi MARA (ITM), Shah Alam concerning ITM's main entrance to Kolej Seroja by using Virtual Geographic Information System (VGIS) concept. To perform this project, three dimensional (3D) graphic software and Internet technology have been using to visualize the two dimensional (2D) ITM's map into 3D virtual object that similarly to the physical site. The user can virtually tour to the location and get the information, just from their computer that link to the Internet without going to the campus physically.